Regional Identity and Multiculturalism: the Baltic Germans of Latgale in the Early 20th Century Latvian Literature - Romanovska, Alina (Respectus Philologicus, 2021)
In the studies of Latvian culture and history, there is a number of investigations dedicated to the influence of Baltic German culture on Latvian culture. Hence the Latgale region was not given due attention in this regard. The role of the Baltic Germans in this region is peculiar due to its specific history, and it is important to study how the Baltic German culture influences the multicultural identity of Latgale. A project of the Latvian Science Council The Baltic Germans of Latgale in the context of socio-ethnic relations from the 17th until the beginning of the 20th century (2020–2021) is devoted to this topic. One of the tasks of the project is the analysis of the image of the Baltic Germans in fiction. In the framework of the research, the works written in the Latvian literary language, the action of which is set in Latgale, are analysed. The focus is on fictional works about Latgale written by two authors – Antons Austriņš (1884–1934) and Ādolfs Ers (1885–1945) – in the first and second decades of the 20th century. The said writers are the first currently distinguished authors narrating in the Latvian literary language, who describe Latgale in a number of their works. Compared to other nationalities (Poles, Russians, Jews), the Baltic Germans are mentioned minimally in their works; moreover, it is a commonplace that in some cases protagonist’s belonging to German descent is not mentioned, which can only be inferred. Although the Baltic Germans belong to the Latgale past, their culture is imperceptibly and harmoniously apparent in Latgale, i.e. it is evident in the castles (castle ruins) and manors as well as in the use of Germanisms by the Baltic Germans, it has determined the location of the Latgale cities and influenced the worldview.
Keywords: regional identity; multiculturalism; Latgale; Baltic Germans; Latvian literature